Collective Bargaining in the Maritime Fishing Industry: Recent Developments - Gurdon, Michael; Wright, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1984)
This paper summarizes recent changes in the Canadian fishing industry, with particular emphasis on the Maritime region, traces the rise of a new union seeking to represent inshore fishermen, and describes the resulting collective bargaining legislation in New Brunswick.